The Influence of Communication Competence, Technological Literacy, and Innovation Climate on Digital Leadership Effectiveness in the Public Service Sector - Firman Aziz; Sri Purwati; Eko Nur Hermansyah; Riesna Apramilda; Elvira M. Usulu; Itot Bian Raharjo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The current research aims to assess the significance of communication competence, technological literacy, and innovation climate on the digital leadership effectiveness in the public service sector. The public sector leaders have to be very much engaged and along with the public, oversee the transformational digital changes in a very inclusive way. In this regard, a quantitative methodology survey was conducted among the 200 selected civil servants and contract workers of the Indonesian public sector. The sampling method was purposive and the respondents had to comply with the criteria regarding the daily operational work involving digital systems, experience in dealing with digital technology-managed leaders, and participation in the public service innovation cycle. The research tools were validated through a t-test and the reliability was measured using Cronbach's Alpha, while the data suitability was examined through classical assumption tests for normality, heteroscedasticity, and multicollinearity, which are the three main factors affecting the data quality. Data analysis was conducted using multiple linear regression to examine the simultaneous and partial effects between variables. The results showed that all three independent variables had a positive and significant effect on digital leadership effectiveness. Practically, the results can serve as a basis for the government in developing strategies to improve digital leadership competency through communication training, technological literacy, and the creation of an innovative climate within the bureaucracy.